Analisis Tingkat Kedisiplinan Siswa Dalam Mengikuti Pembelajaran Daring Di SMA PGRI 2 Palembang - Afriansyah, Diman; Putri, Ramtia Darma (BKI IAIN Pontianak, 2021)
Abstract: During bold learning, teaching and learning activities (KBM) are currently ineffective, so that subject teachers have difficulty in paying attention to students optimally and make many students absent, late in collecting assignments, not paying attention to learning and late logging in to the quipper account ( Online Media), The purpose of the researcher is to determine the discipline of students in participating in learning at SMA PGRI 2 Palembang. The type of research used is descriptive qualitative. Where the researcher collects as much data as possible, both from reference books, journals, interviews with relevant sources and going directly to the field to get results that are in accordance with the title that you want to examine both in oral and written forms. The discipline aspect in brave learning during the covid-19 pandemic at SMA PGRI 2 Palembang almost met the criteria but there were some who did not meet the criteria, including students who were not able to divide their time, had not been able to take advantage of study time, and some students did not collect assignments on time. The obstacles faced by students in learning challenges are a) network problems and internet quotas, b) access to smartphone and computer technology, c) home disturbances. So that students are enthusiastic in learning and able to overcome all bad possibilities in learning during the covid-19 pandemic. So that teachers can serve as much as possible, be able to overcome student discipline problems in learning to be brave through programs that are considered to stimulate the spirit of learning, students make it easier for students to learn.